Climate, environment and human behaviour in the Middle Palaeolithic of Abrigo de la Quebrada (Valencia, Spain): The evidence from charred plant and micromammal remains - Carrión Marco, Yolanda (2020)
The Abrigo de la Quebrada rock shelter was occupied by Neanderthal groups during the early Upper Pleistocene, yielding evidence for their subsistence practices and local resource exploitation. This paper focuses on the plant macroremains and the micromammals, which provide information about occupation patterns, the surrounding landscape, the use of resources, and the environment. Mountain pine forests and permanent grass formations containing humid zones and open spaces that would have harboured an eurythermal microfauna were the dominant landscape type. Cold-climate pines provided most of the firewood. The data are consistent with a recurrent, seasonal occupation pattern, in which the rock shelter was used for short periods in the context of an annual round characterized by a high degree of mobility.